Gentrification and the enterprise culture Britain, 1780-1980 - Thompson, F. M. L. (Francis Michael Longstreth) (Ford lectures, 2001)
In this book, the author, with his typical blend of elegance and erudition, makes an incisive contribution to the longstanding debate over gentrification and entrepreneurialsim in Britain.